Miracles and mysteries of breast milk: from Egyptians to the 3 M's (Metabolomics, Microbiomics, Multipotent stem cells) - Vassilios Fanos; Roberta Pintus; Alessandra Reali; Angelica Dessì (Hygeia Press di Corridori Marinella, 2017)
The ancient Egyptians considered breast milk the nectar of Gods that could give life, strength and ensure a very long existence. Nowadays, it is well known that breast milk is a dynamic bioactive mixture that is tailored upon the needs of the neonates. In fact breast milk contains nutritional substances (such as lipids, carbohydrates, proteins, vitamins and minerals), bioactive substances (such as hormones, cytokines, chemokines, immunoglobulins, leucocytes) and, according to the newest works, bacteria (microbiome of maternal milk) and multipotent stem cells. Metabolomics is one of the newest "omics" sciences that make it possible to have a snapshot of the metabolic state of an individual or a biufluid. Now about 10 papers have been published in the last 3 years on metabolomics in human milk. Human breast milk was mistakenly thought to be sterile for almost a century, but nowadays using the modern technologies it is well known that it is "contaminated": in fact investigators we know that bacteria can be found in breast milk speaks about maternal milk microbiota. A breastfed baby is thought to ingest up to 10 milions of live bacteria per day.  There are as much as 600 species of bacteria in maternal milk. The possible future applications of stem cells found in are potentially endless: a tailored regenerative medicine with less ethical problems and better outcomes for the patients could be developed.